Melanins as Sustainable Resources for Advanced Biotechnological Applications. Issue 2 (25th November 2020) - Galeb, Hanaa A.; Wilkinson, Emma L.; Stowell, Alison F.; Lin, Hungyen; Murphy, Samuel T.; Martin‐Hirsch, Pierre L.; Mort, Richard L.; Taylor, Adam M.; Hardy, John G.
Abstract: Melanins are a class of biopolymers that are widespread in nature and have diverse origins, chemical compositions, and functions. Their chemical, electrical, optical, and paramagnetic properties offer opportunities for applications in materials science, particularly for medical and technical uses. This review focuses on the application of analytical techniques to study melanins in multidisciplinary contexts with a view to their use as sustainable resources for advanced biotechnological applications, and how these may facilitate the achievement of the United Nations Sustainable Development Goals. Abstract : Melanin‐based materials have broad applicability in materials science and engineering for medical and technical applications. This review offers an overview of the techniques used to analyze their chemical, electrical, optical, and paramagnetic properties with a view to their use as sustainable resources for advanced biotechnological applications that may help the achieve the United Nations Sustainable Development Goals.